A STUDY OF PHYTOCHEMICAL CONSTITUENTS IN CARALLUMA QUADRANGULA - Al-Mahweety, Jamal A. N.; Azzam, Sadeq HS; Alyahawi, Ali (Universal Journal of Pharmaceutical Research, 2020)
Objectives: Caralluma belongs to the family Asclepiadaceae, native to the Indian sub-continent have different medicinal properties and used in folk medicine as remedies to treat wide variety of diseases and health conditions. Objective of present study was to isolate, analyze and identify the phytochemicals composition from steam of Caralluma quadrangula. Methods: Extractions of the chemical components was carried out by different chromatographic techniques. The phytochemical characterizations were evaluated by nuclear magnetic resonance and mass spectrometry. Results: The quantitative phytochemical analysis of this species exhibited the presence of three compounds, Glochidonol (5gm), Dihydroxy-14-pregn-5-en-20-one (9.8gm), Hydroxystigmast-5-en-7-one (7.8gm) and Stigmasterol (5.7 mg). Hydroxystigmast-5-en-7-one, report from Caralluma quadrangula stem as first time. Conclusion: The present study is strengthen for the discovery three pure chemical compounds from C. quadrangula. Peer Review History: Received 4 February 2020; Revised 9 March; Accepted 27 April; Available online 15 May 2020 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Ahmad Najib , Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Dr. Hatem Sameir Abbas , Al-Azhar University, Egypt, hsam8406@yahoo.com